Equações diferenciais aplicadas a escoamento de fluidos - Silva, Luis Felipe Alexandre da (Universidade Federal Rural do Semi-Árido, 2019)
Many problems in the science and technological fields are modeled by differential equations. This study will show that even first order equations and simple solution equations have important applications, providing a mathematical forecast model for a variable mass system comprised of fluids stored in a reservoir. The fluids were subject to drainage, having as a differential, the qualitative and quantitative analysis of the variables when drained in a drain with variable area. Drainage studies were conducted in cylindrical tanks, rectangular tanks, funnels and truncated cones, where they were modeled by differential equations that when solved, provided the level variation performance of the liquid in each tank.
Differential equations applied to fluid flow
Monografia
Keywords: Dreno variável; Sistema de massa variável; Variação de nível; Variable drain; Variable mass system; Level variation; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA